Evidence-Based Endothelial Rehabilitation. (2nd January 2017) - Liu, Shaohui; Veldman, Peter
ABSTRACT: Endothelial keratoplasty (EK) has replaced penetrating keratoplasty (PKP) as the preferred surgical therapy for corneal endothelial dysfunction. However, recent nationwide corneal graft registry data showed few advantages to EK relative to PKP with respect to graft survival and visual outcomes. This article compares the published outcomes and complications of EK to those of PKP. EK demonstrates superior spectacle corrected visual outcomes, fast recovery, less graft rejection, and higher patient satisfaction, particularly in studies performed by high-volume surgeons/centers. Endothelial cell loss in EK, while higher at early time points, was equivalent or superior at five-years' follow-up and graft survival was equivalent to or superior to PKP in these centers/studies. Continued standardization and simplification of EK procedures may allow surgeons who perform a lower volume of EK to achieve results that mirror those of high-volume centers/surgeons and close the potential gap in outcomes demonstrated in the registry data.